2014
DOI: 10.1139/cjp-2013-0177
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluorescence quenching on 6BAAC in different solvents

Abstract: The fluorescence quenching studies of 6-bromo-3-azidoacetyl coumarin (6BAAC) by aniline in four different solvents, namely acetonitrile, benzene, dioxane, and toluene, were carried out at room temperature to understand quenching mechanisms. The Stern-Volmer plots have been found to be nonlinear with a positive deviation for all the solvents studied. To interpret these results we have invoked the ground state complex formation and sphere of action static quenching models. Using these models various quenching ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…In our case, the S–V plot displayed upward curvature for the 2AHBC molecule in all the solvents and is shown in Figure . The upward curve in the S–V plot indicated the existence of static quenching either due to ground state complex formation or the sphere of action static quenching model . Similar results were consistent with previous reports in the literature …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In our case, the S–V plot displayed upward curvature for the 2AHBC molecule in all the solvents and is shown in Figure . The upward curve in the S–V plot indicated the existence of static quenching either due to ground state complex formation or the sphere of action static quenching model . Similar results were consistent with previous reports in the literature …”
Section: Resultssupporting
confidence: 93%
“…In this model, the non‐linearity in the S–V plot can be explained either due to ground state complex formation or the sphere of action static quenching model …”
Section: Theorymentioning
confidence: 99%
“…The obtained results were correlated with the literature. It is observed that the calculated values of encounter distance ( R ) are almost double the kinetic distance ( r ) in all of the binary solvent mixtures. This demonstrates that the present work obeys the sphere of action model and hence confirms the presence of static quenching reactions. However, static effects can also be evident from diffusion-limited reactions .…”
Section: Resultsmentioning
confidence: 99%
“…[30] Dynamic quenching involves diffusion of quencher into fluorophore while the duration of excited state lifetime and hereafter, fluorophore goes back to ground state with no emission of photon. [31][32][33][34][35][36] This in turn affects lifetime of fluorophore in the excited state. When a non-linear variation is observed in Stern-Volmer plot, it could be an indication of the quenching mechanism not being solely dynamic.…”
Section: Effect Of Cobalt Chloride Concentration On Emission Spectrum...mentioning
confidence: 99%